Problematika Pemenuhan Hak Positif Tersangka terhadap Pelanggaran Pasal 143 Ayat (4) KUHP - Eldy Noerdin (Jurnal Hukum Lex Generalis, 2025)
Article 143 paragraph (4) of the Indonesian Criminal Procedure Code (KUHAP) regulates the positive rights of suspects, which must be fulfilled by the public prosecutor even if not requested. However, in criminal justice practice, this provision is often ignored as suspects only receive the indictment without the case files. Research shows that efforts to enforce this right through a pretrial process are hindered by the time limit in Article 82 paragraph (1) letter d of KUHAP and Constitutional Court Decision No. 102/PUU-XIII/2015. Efforts to raise objections during trial regarding violations of this right are often blocked by the belief that such objections are outside the scope of Article 156 paragraph (1) of KUHAP. The research concludes that judges must determine the legal consequences of violating Article 143 paragraph (4) of KUHAP.